2013
DOI: 10.21533/pen.v1i2.21
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Corrosion Behaviors in 3.5% NaCl Solution of Grade-A and Dual-Phase Steels Welded by FCAW

Abstract: Abstract:The first aim of this study is to demonstrate the transformation of Grade-A steel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, a morphology made up of islands of martensite in continuous ferrite matrix proves to be more corrosion-resistant compared to morphologies such as ferrite-chain martensite, uniform fine fibrous ferrite-martensite and uniform fibrous ferrite-martensite with an almost similar amount of martensite in the structure. The corrosion resistance of dual-phase steel increases depending upon the increase in the volume fraction of martensite, and in particular of its morphological features [10]. In this reference, it is reported that the corrosion resistance of the DP steel increases with intercritical annealing tempering heat treatment.…”
Section: Noise Resistancementioning
confidence: 91%
See 1 more Smart Citation
“…However, a morphology made up of islands of martensite in continuous ferrite matrix proves to be more corrosion-resistant compared to morphologies such as ferrite-chain martensite, uniform fine fibrous ferrite-martensite and uniform fibrous ferrite-martensite with an almost similar amount of martensite in the structure. The corrosion resistance of dual-phase steel increases depending upon the increase in the volume fraction of martensite, and in particular of its morphological features [10]. In this reference, it is reported that the corrosion resistance of the DP steel increases with intercritical annealing tempering heat treatment.…”
Section: Noise Resistancementioning
confidence: 91%
“…The corrosion resistance of the DP steel increases with intercritical annealing tempering heat treatment. In addition, it has been reported that the dual-phase steel tempered at higher temperature of 800 • C (martensite island morphology in the ferrite matrix), had better corrosion resistance properties than the dual-phase steel tempered at lower temperature of 730 • C, which consists of fibrous ferrite and martensite [10]. Abedini et al [11] mentioned that an increase in martensite amount does not favor the corrosion rate of DP steels.…”
Section: Introductionmentioning
confidence: 99%